A Comparative Study on The Adsorption Behavior of Congo Red on to ZnAl and ZnCr Layered Double Hydroxides - Tarmizi Taher; Nyanyu Ummu Hani; Neza Rahayu Palapa; Risfidian Mohadi; Aldes Lesbani (Chemistry Department, The University of Brawijaya, 2020)
In this work, two synthetic layered double hydroxides (LDH) consists of Zn2+ as M2+ cation with different M3+ cation, i.e., Al3+ and Cr3+ were used as an adsorbent for Congo Red removal aqueous solution. Both Zn-Al and Zn-Cr LDH were characterized by X-ray diffraction, FT-IR, and BET surface area analyzer. The effect of contact time, initial dye concentration, and temperature were evaluated in a batch technique in order to investigate the characteristic of Congo Red adsorption onto both adsorbents. The experimental data were assessed according to the parameter of adsorption kinetics, isotherm, and thermodynamics. The results of LDH characterization showed that Zn-Al LDH has a higher interlayer distance than Zn-Cr LDH, although Zn-Cr LDH has a higher surface area. The FT-IR analysis indicated the interlayer space of both Zn-Cr and Zn-Al LDH was dominated by CO32- as the interlayer anion species. The adsorption kinetics study of Congo Red on both LDH revealed that the adsorption process followed the pseudo-second-order model. For the adsorption isotherm, the experimental data fit well with the Freundlich model rather than the Langmuir model. The thermodynamic study indicated that the adsorption process that occurred on both adsorbents was spontaneous with exothermic nature.